A Sensorimotor Signature of the Transition to Conscious Social Perception: Co-regulation of Active and Passive Touch - Kojima, Hiroki; Froese, Tom; Oka, Mizuki; Iizuka, Hiroyuki; Ikegami, Takashi (Frontiers in Psychology, 2017)
It is not yet well understood how we become conscious of the presence of other people as being other subjects in their own right. Developmental and phenomenological approaches are converging on a relational hypothesis: my perception of a ‘you’ is primarily constituted by another subject’s attention being directed towards ‘me’. This is particularly the case when my body is being physically explored in an intentional manner. We set out to characterize the sensorimotor signature of the transition to being aware of the other by re-analyzing time series of embodied interactions between pairs of adults (recorded during a “perceptual crossing” experiment). Measures of turn-taking and movement synchrony were used to quantify social coordination, and transfer entropy was used to quantify direction of influence. We found that the transition leading to one’s conscious perception of the other’s presence was indeed characterized by a significant increase in one’s passive reception of the other’s tactile stimulations. Unexpectedly, one’s clear experience of such passive touch was consistently followed by a switch to active touching of the other, while the other correspondingly became more passive, which suggests that this intersubjective experience was reciprocally co-regulated by both participants.